The home office and the ergonomic impacts resulting from the pandemic in an academic community of a Brazilian educational institution (Research, Society and Development, 2022)
In the current scenario of public health crisis, the work environment has become the Home Office. The present article has the objective of performing a case study, in the form of an opinion survey, about the ergonomics of the academic community of a higher education institution that started to work in a home office regime, aiming to study the impacts related to the transition from work outside the home to the home office due to the COVID-19 pandemic. The present work consists of a descriptive research of the case study type using a form, whose data were treated quantitatively and qualitatively. The methodology of this study was divided into the following steps. The first stage consisted of the literature review, whose objective was to find documents and scientific productions relevant to the topic discussed in this article. Then, a Google Forms form was created, to be directed to the academic community (teachers and administrative technicians) of the Polytechnic School of Pernambuco - POLI/UPE. After completing the application of the form, the information collected was treated according to the Bardin Method. Among the employees of the analyzed EI, 88% reported complaining of pain in at least one part of the body while working in the home office model, even though 55% of them previously considered that the ergonomic conditions of their respective workstations were "good or excellent". Among the complaints, neck pain (64.4% of the cases), stand out.